Application of combined positron emission tomography and computed tomography in the diagnosis of recurrent gastrointestinal stromal tumor and assessment of the efficacy of imatinib therapy – a case raport - Kula, Zbigniew; Szefer, Jarosław; Małkowski, Bogdan (Contemporary Oncology/Współczesna Onkologia, 2006)
Combined positron emission tomography and computed tomography (PET/CT) with the use of F-18-fluorodeoxyglucose (FDG) is one of the most modern imagining methods producing images of the entire body or selected human organs. This article presents the case of a 51-year-old woman with gastrointestinal stromal tumors (GIST). The clinical diagnosis was confirmed by the immunohistological examination of postoperative specimens. The patient underwent an operation because of recurrence. The diagnosis of disease recurrence was confirmed by a PET/CT examination. The patient was treated with imatinib in doses of 400 mg because of inoperable/metastatic GIST. The control PET/CT examination after 8 weeks showed a partial response of the imatinib therapy. The presented case confirmed the usefulness of the PET/CT diagnostics in the assessment of the recurrent gastrointestinal stromal tumors after surgery and the efficacy of imatinib therapy.